2023
DOI: 10.1002/ibra.12094
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine as a therapeutic agent in major depressive disorder and posttraumatic stress disorder: Potential medicinal and deleterious effects

Abstract: Major depressive disorder (MDD) and posttraumatic stress disorder (PTSD) are the most common causes of emotional distress that impair an individual's quality of life. MDD is a chronic mental illness that affects 300 million people across the world. Clinical manifestations of MDD include fatigue, loss of interest in routine tasks, psychomotor agitation, impaired ability to focus, suicidal ideation, hypersomnolence, altered psychosocial functioning, and appetite loss. Individuals with depression also demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 95 publications
(217 reference statements)
0
2
0
Order By: Relevance
“…While it is known that microplastics can easily enter our body (Figure 2) by the routes of ingestion, inhalation, and dermal contact, the health risks associated with each pathway are still not well understood. There is also a need for more research and development studies to find and comprehend the longstanding and enduring consequences of the exposure to microplastics on our brain as well as mental health, pre-and post-natal developmental effects, various neurological disorders like Alzheimer's disease [158], epilepsy [159], and other neuropsychological conditions [160][161][162]. While studies have shown potential risks such as inflammation, oxidative stress, and damage to organs, there is still much to be learned about the cumulative effects of exposure over time.…”
Section: Future Directionsmentioning
confidence: 99%
“…While it is known that microplastics can easily enter our body (Figure 2) by the routes of ingestion, inhalation, and dermal contact, the health risks associated with each pathway are still not well understood. There is also a need for more research and development studies to find and comprehend the longstanding and enduring consequences of the exposure to microplastics on our brain as well as mental health, pre-and post-natal developmental effects, various neurological disorders like Alzheimer's disease [158], epilepsy [159], and other neuropsychological conditions [160][161][162]. While studies have shown potential risks such as inflammation, oxidative stress, and damage to organs, there is still much to be learned about the cumulative effects of exposure over time.…”
Section: Future Directionsmentioning
confidence: 99%
“…As the field of nanomedicine continues to advance, personalized medicine approaches are becoming increasingly feasible [34][35][36][37][38]. By tailoring nanoparticle-based therapies to the unique genetic and molecular characteristics of individual patients, the prospects for improved outcomes in CNS cancer therapy are substantial [39][40][41][42].…”
Section: The Prospects Of Personalized Nanomedicinementioning
confidence: 99%
“…Brain tissues from Alzheimer's patients also contained fungal chitin [15]. AD is one of the most recurrent neurodegenerative disorders that affect a person's language acquisition, perception, memory, and thoughts [16][17][18][19][20][21][22][23][24][25], which leads to overall impaired cognition [26,27]. Additionally, those with multiple sclerosis had chitin deposition.…”
Section: Introductionmentioning
confidence: 99%